Comparison of microalbuminuria and heart rate variability in prediction of cardiovascular complications in diabetic population: a pilot study - Deepalakshmi, K.; Vijayabaskaran, S.; Murali, A. (International Journal of Advances in Medicine, 2017)
Background: Microalbuminuria is considered as an early marker and strongly associated with risk of cardiovascular complications in diabetic patients. Autonomic imbalance due to micro vascular damage to parasympathetic and sympathetic fibers results in reduced heart rate variability; also predicts increased risk for cardiovascular events in diabetics. Hence it is necessary to identify an early and effective predictor of diabetic micro vascular complications. Objective of the study was to compare heart rate variability of controls with type 2 diabetes with and without microalbuminuria. Methods: This comparative study was conducted among individuals without diabetes, hypertension and dyslipidemia (controls) and Type II diabetics with and without microalbuminuria (cases). Cases and controls were subjected to general clinical examination; microalbuminuria and HbA1C were noted. heart rate variability was assessed using digital physiograph. Frequency (HF, LF, LF/HF ratio) domain readings were noted. Results: Mann Whitney U test was employed to analyze nonparametric data. Diabetics with microalbuminuria when compared with controls showed statistically significant (p-value=0.015) reduction in vagal activity. When compared with diabetics without microalbuminuria (180.4±151.7) they showed reduction in HF with no statistical significance. When diabetic group without microalbuminuria (0.56±0.31) was compared with controls they showed alternation in LF/HF ratio which has no statistical significance. Diabetics with microalbuminuria when compared with controls showed a statistically significant (p-value=0.009) alternation in LF /HF ratio implying an autonomic imbalance. Conclusions: This study shows there is significant vagal inhibition and autonomic imbalance in diabetic patients with microalbuminuria compared to controls. To ascertain the role of HRV as an early predictor of cardiovascular complications we propose to conduct study with a larger sample size in future.